2018
DOI: 10.1017/s0022215118000695
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary outcomes of endoscopic middle-ear surgery in 103 cases: a UK experience

Abstract: Our results confirm that endoscopic middle-ear surgery is safe, and the short-term outcomes are comparable with conventional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 9 publications
4
18
0
1
Order By: Relevance
“…‡ Success rates for TM closure were 69% to 100% (median, 88%). 4,5,7,9-16,24-36,38 Similar results were obtained from the data of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…‡ Success rates for TM closure were 69% to 100% (median, 88%). 4,5,7,9-16,24-36,38 Similar results were obtained from the data of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…6 The combination of thin rigid otoendoscopes and full highdefinition camera systems has brought about a less-invasive transcanal approach to the middle ear with clear and high contrast views. 7 Transcanal endoscopic ear surgery (TEES) provides a wider view of the surgical field, increased visibility around target objects, and less hidden space. Tympanoplasty (myringoplasty) is a standard surgical procedure used to repair the tympanic membrane (TM) and improve hearing status.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing our results with the studies of Marchioni et al and Yiannakis et al reveals our complication rate to be higher. 8,10 A possible explanation is the small number of cases used in our study (compared with 825 cases used by Marchioni et al and the 103 cases used by Yiannakis et al).…”
Section: Discussionmentioning
confidence: 71%
“…6 Although Kanona et al reported a significant air bone gap improvement with EES compared with traditional methods, 7 this result could not be replicated in a subsequent study. 8 Limitations of TEES have been discussed in the literature in order to refine this surgical technique. Swarup et al found most otologists expressed the need for better instruments in EES to improve the view of the difficult areas in the middle ear and to remove cholesteatomas, 9 arising from the onehanded method during TEES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation